Effects of assurance scope and levels and perceived business reputation on consumers' behaviours. - Goh, Seng Yee. (2008)
This project explores the effects of assurance scope and levels and perceived business reputation on consumers’ behaviours, namely, consumers’ confidence to transact, intentions to purchase and seek compensation.